Expressão e localização de receptores Toll-like -1, -2, -4 e -6 em membranas corioamnióticas de gestações complicadas por corioamnionite histológica - Moço, Natália Prearo [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Acute chorioamnionitis is a response to microbial infection of the amniotic fluid. The innate immune system constitutes the host’s first line of defense against pathogens and, in this regard, Toll-like receptors (TLRs) are important regulators of such nonspecific response. However, the expression of these receptors in chorioamniotic membranes in pregnancies complicated by chorioamnionitis has not been well established. Objective:The purpose of this study was to examine the localization of TLR-1, TLR-2, TLR-4 and TLR-6 in fetal membranes and determine whether histologic chorioamnionitis is associated with changes in gene expression of these receptors. One hundred and fifteen chorioamniotic membranes were included in the study. They were collected at the Obstetrics Service of the Botucatu Medical School, São Paulo State University, UNESP, from pregnant women with preterm delivery or term delivery with or without labor. Both groups were stratified on the basis of the presence of histologic chorioamnionitis. Fragments of the chorioamniotic membranes were sent for histopathologic analysis in order to confirm histologic chorioamnionitis. Other membranes fragments measuring 1cm2 were placed into RNA later and submitted to total RNA extraction. After RNA extraction, the samples with concentration between 0.02 and 0.2 g/L of RNA were submitted to cDNA collection for later use in quantifying the expression of TLR-1, TLR-2, TLR-4 and TLR-6 by the real-time PCR technique using the TaqMan® Gene Expression Assays System. All membranes analyzed expressed TLR-1 and TLR-4, whereas 99.1% expressed TLR-2 and 77.4% expressed TLR-6. TLR-1 and TLR-2 expression were statistically higher in the membranes of preterm pregnancies in the presence of chorioamnionitis as compared with preterm membranes in the absence of the inflammatory infiltrate. Among the membranes of term pregnancies, there was... (Complete abstract click electronic access below)
Keywords: Microbiologia; Imunologia; Gravidez; Toll-like receptor